Hegel and mind : rethinking philosophical psychology - Winfield, Richard Dien, 1950- (Basingstoke, England ; New York : Palgrave Macmillan, 2010)
"Exploring Hegels philosophical psychology to uncover viable remedies to the chief dilemmas plaguing contemporary philosophy of mind, Hegel and Mind exposes why mind cannot be an epistemological foundation nor reduced to discursive consciousness not modelled after computing machines"--Provided by publisher.
Hegel's challenge to the philosophy of mind -- Hegel's solution to the mind-body problem -- Hegel, mind, and mechanism : why machines have no psyche, consciousness, or intelligence -- Self-consciousness and intersubjectivity -- From representation to thought : reflections on Hegel's determination of intelligence -- The psychology of will and the deduction of right : rethinking Hegel's theory of practical intelligence -- Beyond the sociality of reason : from Davidson to Hegel.
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Hegel, Georg Wilhelm Friedrich; Philosophy of mind; Geist; Philosophische Psychologie; Leib-Seele-Problem.; Philosophy of Mind